Oligomer-targeting with a conformational antibody fragment promotes toxicity in Aβ-expressing flies - Wacker, Jessica (BioMed Central, 2014)
INTRODUCTION: The self-assembly of Aβ peptides into a range of conformationally heterogeneous amyloid states represents a fundamental event in Alzheimer’s disease. Within these structures oligomeric intermediates are considered to be particularly pathogenic. To test this hypothesis we have used a conformational targeting approach where particular conformational states, such as oligomers or fibrils, are recognized in vivo by state-specific antibody fragments. RESULTS: We show that oligomer targeting with the KW1 antibody fragment, but not fibril targeting with the B10 antibody fragment, affects toxicity in Aβ-expressing Drosophila melanogaster. The effect of KW1 is observed to occur selectively with flies expressing Aβ(1–40) and not with those expressing Aβ(1–42) or the arctic variant of Aβ(1–42) This finding is consistent with the binding preference of KW1 for Aβ(1–40) oligomers that has been established in vitro. Strikingly, and in contrast to the previously demonstrated in vitro ability of this antibody fragment to block oligomeric toxicity in long-term potentiation measurements, KW1 promotes toxicity in the flies rather than preventing it. This result shows the crucial importance of the environment in determining the influence of antibody binding on the nature and consequences of the protein misfolding and aggregation. CONCLUSIONS: While our data support to the pathological relevance of oligomers, they highlight the issues to be addressed when developing inhibitory strategies that aim to neutralize these states by means of antagonistic binding agents.